EPCT-09. ROVER: A phase 1/2 study of avapritinib in pediatric patients with solid tumors dependent on KIT or PDGFRA signaling. (3rd June 2022) - Chi, Susan; Hsieh, Antony; Foley, Megan; Shi, Hongliang; Swamy, Preethi; Rodstrom, Jill; Rudoltz, Marc
Abstract: Prognosis for pediatric patients with advanced relapsed/refractory (R/R) solid (including central nervous system [CNS]) tumors is poor. KIT alterations are common in germ cell tumors and high-grade glioma (HGG); platelet-derived growth factor receptor alpha ( PDGFRA ) alterations are common in sarcoma and HGG. H3K27M -mutant gliomas are dependent on PDGFRA signaling. No KIT/PDGFRA targeted therapies are currently approved for pediatric patients with R/R solid or CNS tumors, or H3K27M -mutant gliomas. Selective KIT and PDGFRA inhibitor avapritinib demonstrated potent activity against KIT activation-loop (exon 17), juxtamembrane (exon 11), and extracellular-domain (exon 9) mutants (IC50 <2 nM), and PDGFRA activation-loop (D842V) mutants (IC50 =0.24 nM); cellular IC50 of PDGFRA wild-type was 95 nM. CNS penetration in preclinical models (steady-state brain-to-plasma ratios ranging from 0.74–1.00) has demonstrated potential for CNS antitumor activity. Avapritinib is approved in the USA to treat adults with unresectable/metastatic gastrointestinal stromal tumors (GIST) harboring PDGFRA exon 18 mutations (including D842V), and adults with advanced systemic mastocytosis. In the EU, avapritinib is approved for adults with unresectable/metastatic GIST harboring a PDGFRA D842V mutation. Objectives of ROVER 2-part phase 1/2, multicenter, open-label study (NCT04773782) are avapritinib safety, preliminary efficacy, and pharmacokinetics in pediatric patients aged 2 to <18 years with solid R/R tumors dependent on KIT or PDGFRA signaling, including H3K27M -mutant gliomas, and no alternative treatment options. Part 1 will enroll ≥12 patients; primary endpoint is confirmed age and body surface area physiologically based pharmacokinetic modeling predicted dose to provide equivalent exposure to the 300 mg adult avapritinib dose. Part 2 will enroll ≥25 patients at the recommended avapritinib dose from Part 1; the primary endpoint is objective response rate. Avapritinib once-daily will be administered in continuous 28-day cycles. Enrollment in this study is planned at 26 sites in 10 countries, including centers in North America, Europe, and Asia/Pacific.